Different Faces: Different Facelift Techniques - Sedgh, Jacob; Fedok, Fred G. (Facial Plastic Surgery, 2020)
The introduction and evolution of different rhytidectomy techniques has spawned an exciting era of facial rejuvenation in modern times. To provide patients with the best customized approach to surgery the facial aesthetic surgeon must have familiarity and understanding of the fundamental differences between these techniques. Here we set forth to provide some historical and anatomical perspective, followed by reviewing and comparing some of the key aspects of the most commonly utilized facelift techniques.
Keywords: rhytidectomy; facelift; deep plane facelift; SMAS; MACS lift